Secure Information Exchange Without Prior Key Distribution via Single-photon Hyperstates - An, Nguyen Ba (Communications in Physics, 2022)
Methods for two distant parties to exchange their secret messages using single photons are considered. There existed several such methods but they are either insecure or face with information leakage problem. Recently, Ye et al. [Quantum Inf. Process. 20 (2021) 209] have reported a method using single photons in both polarization and spatial degrees of freedom that is both efficient and resistant from information leakage. However, this method is not so feasible as it has specific limitations, namely, it requires availability of quantum memory and high classical communication cost. We propose in this paper a new method to overcome the above-said limitations. Our method is also efficient because we also use single photons in two degrees of freedom. However, the encoding operation in our method is modified so that no quantum memory is demanded at all and the execution of our method is simpler compared to the method of Ye et al. Moreover, the cost of classical communication in our method is 50% cheaper than that in the method of Ye et al. Therefore, our method proves to be feasible, simple and economical that could be realized by means of current technologies.